Regulatory T Cells License Macrophage Pro-Resolving Functions During Atherosclerosis Regression. Issue 3 (17th July 2020) - Sharma, Monika; Schlegel, Martin P.; Afonso, Milessa S.; Brown, Emily J.; Rahman, Karishma; Weinstock, Ada; Sansbury, Brian E.; Corr, Emma M.; van Solingen, Coen; Koelwyn, Graeme J.; Shanley, Lianne C.; Beckett, Lauren; et al.
Abstract : Rationale: Regression of atherosclerosis is an important clinical goal; however, the pathways that mediate the resolution of atherosclerotic inflammation and reversal of plaques are poorly understood. Regulatory T cells (Tregs) have been shown to be atheroprotective, yet the numbers of these immunosuppressive cells decrease with disease progression, and whether they contribute to atherosclerosis regression is not known. Objective: We investigated the roles of Tregs in the resolution of atherosclerotic inflammation, tissue remodeling, and plaque contraction during atherosclerosis regression. Methods and Results: Using multiple independent mouse models of atherosclerosis regression, we demonstrate that an increase in plaque Tregs is a common signature of regressing plaques. Single-cell RNA-sequencing of plaque immune cells revealed that unlike Tregs from progressing plaques that expressed markers of natural Tregs derived from the thymus, Tregs in regressing plaques lacked Nrp1 expression, suggesting that they are induced in the periphery during lipid-lowering therapy. To test whether Tregs are required for resolution of atherosclerotic inflammation and plaque regression, Tregs were depleted using CD25 monoclonal antibody in atherosclerotic mice during apolipoprotein B antisense oligonucleotide-mediated lipid lowering. Morphometric analyses revealed that Treg depletion blocked plaque remodeling and contraction, and impaired hallmarks of inflammation resolution, including dampening of the T helper 1 response, alternative activation of macrophages, efferocytosis, and upregulation of specialized proresolving lipid mediators. Conclusions: Our data establish essential roles for Tregs in resolving atherosclerotic cardiovascular disease and provide mechanistic insight into the pathways governing plaque remodeling and regression of disease. Abstract : Supplemental Digital Content is available in the text.